2016
DOI: 10.17795/ijcp-3910
|View full text |Cite
|
Sign up to set email alerts
|

Developing a WebGIS for Geo-Visualization of Cancer

Abstract: BackgroundConsidering the hygiene facilities and sharing the data of diseases, considerable attempts to promote the public awareness have been made by various media; however, most of the provided information is based on numerical and verbal statistics, and may not provide suitable understanding for people in regard with the situation of diseases.ObjectivesThe main aim of this study is to design an interactive WebGIS system in which people could simply produce and observe their favorite maps of different cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This technology can provide high-resolution environmental characteristics, and researchers could use this first-hand information to model contextual and environmental risk (e.g., air pollution) and protective factors (e.g., access to publicly open green and blue spaces). However, despite of Web-GIS potential for real-time data management, query, and visualization, it is surprising that this review has not found examples of web-based GIS applications in dementia, when there are successful examples of its use for other chronic diseases, such as cardiovascular [139], diabetes [140], or cancer [141].…”
Section: Discussionmentioning
confidence: 97%
“…This technology can provide high-resolution environmental characteristics, and researchers could use this first-hand information to model contextual and environmental risk (e.g., air pollution) and protective factors (e.g., access to publicly open green and blue spaces). However, despite of Web-GIS potential for real-time data management, query, and visualization, it is surprising that this review has not found examples of web-based GIS applications in dementia, when there are successful examples of its use for other chronic diseases, such as cardiovascular [139], diabetes [140], or cancer [141].…”
Section: Discussionmentioning
confidence: 97%
“…The literature shows that absences for voice symptoms are mostly short [ 30 ], whereas those for psychological symptoms tend to last longer [ 14 ]. A study showed that long-term absence from work occurred more often in older teachers [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kienberger et al (2013) [ 29 ] developed a webGIS to spatially visualize vulnerabilities to dengue fever in Cali (Colombia). Khoshabi et al (2016) [ 30 ] developed an interactive webGIS tool to dynamically visualize and analyze cancer data and environmental parameters for a database in Iran. This study also implemented different forms to visualize cancer occurrence in the form of bar and pie charts.…”
Section: Introductionmentioning
confidence: 99%
“…Regions with a positive Z-score and values ≥ 1.96 indicate a higher rate and are considered as hot spots. Likewise, regions with a negative Z-score and values ≤ -1.96 indicate a lower rate and are cold spots (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Statistical Analysesmentioning
confidence: 99%